2023
DOI: 10.18662/lumproc/gekos2022/04
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment and Competitiveness. Evidences from Romanian Economy

Abstract: The activity of companies with foreign capital is more often in the center of attention of the public opinion, researchers and public authorities considering the positive effects but also the negative externalities that it generates on the economies of the host countries. With the liberalization of capital movements, FDI was consider the panacea that could solve all economic, environmental and social problems in the host less developed countries, but the reality is much more complex. In order to test if foreig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Recent studies found that the risk mitigation characteristic of Bitcoin is different among countries, as it depends on the regulatory policies and decisions (Haq et al 2021). Therefore, investors need to take into consideration country and time contexts when using cryptocurrency as a risk management tool (Haq et al 2021;Apostu et al 2023). Researchers revealed that not only the financial and economic factors of a particular country determine the volatility but also the global business cycle and Real Economic Activities Index (Demir et al 2018).…”
Section: Bitcoin Return Relationship With Economic Uncertaintymentioning
confidence: 99%
“…Recent studies found that the risk mitigation characteristic of Bitcoin is different among countries, as it depends on the regulatory policies and decisions (Haq et al 2021). Therefore, investors need to take into consideration country and time contexts when using cryptocurrency as a risk management tool (Haq et al 2021;Apostu et al 2023). Researchers revealed that not only the financial and economic factors of a particular country determine the volatility but also the global business cycle and Real Economic Activities Index (Demir et al 2018).…”
Section: Bitcoin Return Relationship With Economic Uncertaintymentioning
confidence: 99%